Dose requirement and cardiopulmonary effects of diluted and undiluted propofol for induction of anaesthesia in dogs. (March 2021) - Rögels, Hanna; Martinez-Taboada, Fernando
Abstract: Objective: To compare the dose, cardiopulmonary effects and quality of anaesthetic induction in dogs using propofol (10 mg mL –1 ) and diluted propofol (5 mg mL –1 ). Study design: Randomized, blinded, clinical study. Animals: A total of 28 client-owned dogs (12 males/16 females). Methods: Following intramuscular acepromazine (0.02 mg kg –1 ) and methadone (0.2 mg kg –1 ), propofol (UP, 10 mg mL –1 ) or diluted propofol (DP, 5 mg mL –1 ) was administered intravenously (0.2 mL kg –1 minute –1 ) by an anaesthetist unaware of the allocated group to achieve tracheal intubation. Sedation, intubation and induction quality were scored from 0 to 3. Pre- and post-induction pulse rate (PR), respiratory rate ( f R ) and systolic (SAP), mean (MAP) and diastolic (DAP) arterial blood pressure were compared. Time to first breath and induction dose were recorded. Data were analysed for normality and Mann–Whitney U or Student t tests were performed where appropriate. Significance was set at p < 0.05. Data are presented as mean ± standard deviation or median (range). Results: The propofol dose administered to achieve induction was lower in the DP group (2.62 ± 0.48 mg kg –1 ) than in the UP group (3.48 ± 1.17 mg kg –1 ) ( p = 0.021). No difference was observed in pre- and post-induction PR, SAP, MAP, DAP and f R between groups. The differences between post-induction and pre-induction values of these variables were also similar between groups. Time to first breath did not differ between groups. Sedation scores were similar between groups. Quality of tracheal intubation was marginally better with UP 0 (0–1) than with DP 1 (0–2) ( p = 0.036), but overall quality of induction was similar between groups [UP 0 (0–1) and DP 0 (0–1), p = 0.549]. Conclusion and clinical relevance: Diluting propofol reduced the dose to induce anaesthesia without significantly altering the cardiopulmonary variables.